Analytical and Numerical Approach for Estimating Geometry and Performance of Thrust Generating Combustion Chamber - Mahato, Aplesh Kumar; Sharma, Dinanath; Bhaatt, Niraj; Koirala, Rajeshwor; Bastakoti, Durga (Himalayan Journal of Applied Science and Engineering, 2021)
The thrust generation capacity of any propulsion system is heavily dependent upon the geometry, flow, and performance parameters of the system. The performance parameters include temperature, pressure, and velocity estimations at the critical the locations of the systems. For the estimation of geometry and performance of thrust generating combustion chamber analytical and numerical approaches are used. Cases of under-expansion and perfectly expansion for nozzle is analysed with the theoretical calculation from which length and diameter of chamber, throat diameter, nozzle exit area are calculated and obtained as 70 mm, 70.67 mm, 21 mm and 150 mm2, respectively for the case of under-expansion. Likewise, pressures and temperatures in the chamber, throat, and exit of the nozzle are obtained as 71.4556 bar, 40.3 bar, 59.546 bar, and 2243 K, 2238 K, 1103.511 K respectively. This also yielded that the exhaust velocity is supersonic with the value of 476.1 m/s. Values obtained for the case of perfectly expanded nozzle suggests that the geometrical dimensions of nozzles are highly reduces, performance parameters are almost the same and the exhaust velocity is increased by more than 300 %.  Numerical modeling in ANSYS Fluent was performed based on the values suggested by theoretical approach.  Results of numerical modeling were in close resemblance with that of the theoretical approach suggesting validation of the simulation. Pressure, temperatures and velocities at different locations within the combustion chamber are also obtained from numerical modeling.